Prediction of blast-induced window glass fragments - Hao, Hong (2011)
Statistics show that more than 80% human casualties in an explosion event are associated with the failure of glass windows or curtain walls. Owing to the extreme complexity, the current practice in predicting window glass failure and fragments are based mainly on some empirical formulae or simplified numerical simulations. In this study, both empirical and theoretical methods are adopted to calculate the mean fragment area, the mean ejection velocity, and the mean flying distances of the glass fragments to blast loads. Theoretical methods are based on the theory of damage and fracture mechanics while the empirical method is based on either an initial fragment size assumption or an empirical estimation of mean fragment size from field observed data. The results are compared to various injury and lethality, or protection levels specified in codes and security guidelines for personnel protection against glass debris hazards.